Analisis Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Orang Pribadi Dalam Membayar Pajak Penghasilan - Serlinda Afrinita Sari; Hermaya Ompusunggu (Prosiding, 2023)
Taxes are mandatory contributions for individuals or entities to the State that are coercive by law. The purpose of this study was to determine the effect of taxpayer knowledge, taxpayer awareness and tax sanctions on individual taxpayer compliance in paying income tax at KPP Pratama Batam Selatan. The population in this study amounted to 353,894 people with a sample using the slovin formula totaling 100 respondents. This study uses quantitative methods with data quality tests, classical assumption tests, multiple linear regression analysis and hypothesis testing using SPSS 25. From the research that has been done, the results show that using the t test the variables of taxpayer knowledge and taxpayer awareness have a significant effect on compliance taxpayers, while the variable tax sanctions have no significant effect on taxpayer compliance. Then in the f test variable knowledge of taxpayers, awareness of taxpayers and tax sanctions simultaneously affect taxpayer compliance in paying income tax.